Building a New Understanding of Changing Patterns of Community Interaction, Social Behavior, and Conflicts of Interest: A Theoretical Study - Senis, Yotam; Ayorbaba, Musa; Luas, Alfando (Journal of Urban Sociology, 2024)
This theoretical study focuses on developing new understandings of changing patterns of community interaction, social behaviour, and conflicts of interest. This topic is important to study because changes in social interaction and conflicts of interest can have a significant impact on the structure and functioning of society. The methods used in this study include in-depth literature analysis by analyzing various relevant sources and theories. This research also provides observation and interpretation of social phenomena that develop in digital society. The results of this study are expected to provide a deeper understanding of how patterns of social interaction and conflicts of interest develop and change over time, as well as their impact on society. This knowledge is important to assist policymakers and practitioners in understanding and responding effectively to these changes.Keywords: changes in community interaction patterns, social behavior, conflicts of interest, theoretical studies, literature analysis.